Reducing Carbon Footprint through E-government: Towards a Synergy with Renewable Energy and Governance in MENA Countries - Liouane, Naoufel; Akremi, Faten (International Journal of Energy Economics and Policy, 2025)
This study examines how digital government development can reduce CO2 emissions while considering the effects of interaction with renewable energy use and governance quality. Using the Generalised Method of Moments (GMM) in a dynamic panel applied to 13 countries in the MENA region, the results of Westerlund’s cointegration tests reveal no stable long-term relationship between CO2 emissions and the explanatory variables, justifying the adoption of a dynamic difference approach. E-government, as measured by the EGDI index, has an overall positive and significant impact on CO2 emissions, suggesting that digitalisation, in its current state, is responsible for higher energy usage. However, when e-government is incorporated into a strong institutional framework and a green energy strategy, interactions with environmental governance and the deployment of renewable energies overcome this effect. GDP per capita and financial development also contribute to the reduction of CO2. These findings highlight the key role of digital government, which should not be seen as simply technical support activity but rather as a strategic element in the process of pollution control and environmental governance in MENA countries.